2022
DOI: 10.1136/jitc-2022-005128
|View full text |Cite
|
Sign up to set email alerts
|

Effect of CD4+ T cell count on treatment-emergent adverse events among patients with and without HIV receiving immunotherapy for advanced cancer

Abstract: BackgroundThe Food and Drug Administration recommends that people living with HIV (PWH) with a CD4+ T cell count (CD4) ≥350 cells/µL may be eligible for any cancer clinical trial, but there is reluctance to enter patients with lower CD4 counts into cancer studies, including immune checkpoint inhibitor (ICI) studies. Patients with relapsed or refractory cancers may have low CD4 due to prior cancer therapies, irrespective of HIV status. It is unclear how baseline CD4 prior to ICI impacts the proportion of treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 54 publications
1
3
0
Order By: Relevance
“…19,20 We showed that the 24-month incidence rate of irAEs of any grade in this group is comparable with PWH with CD41 T-cell counts >200 cells/mL. Similar findings have been reported by Odeny et al, 17 where the effect of baseline CD41 T-cell counts on the incidence of treatment-emergent adverse events was not modified by HIV status. These data further endorse the need to abrogate arbitrary CD4 cutoffs when using ICIs in the appropriate setting for the treatment of PWH and subsequently reduce barriers to ICI access on the basis of their favorable benefit-to-risk profiles.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…19,20 We showed that the 24-month incidence rate of irAEs of any grade in this group is comparable with PWH with CD41 T-cell counts >200 cells/mL. Similar findings have been reported by Odeny et al, 17 where the effect of baseline CD41 T-cell counts on the incidence of treatment-emergent adverse events was not modified by HIV status. These data further endorse the need to abrogate arbitrary CD4 cutoffs when using ICIs in the appropriate setting for the treatment of PWH and subsequently reduce barriers to ICI access on the basis of their favorable benefit-to-risk profiles.…”
Section: Discussionsupporting
confidence: 89%
“…11 However, recent clinical trials and retrospective studies that included PWH demonstrated that ICIs were active and safe for PWH, although these observations were hampered by small sample sizes and heterogeneous tumor types. [11][12][13][14][15][16][17][18][19][20][21] Given the potential benefit of ICIs in PWH and cancer, 22 larger real-world cohorts are needed to address the existing knowledge gaps, guide clinical decision making, and increase therapeutic opportunities for PWH. Herein, we implement a grassroots effort and assemble a real-world international cohort of PWH who received ICIs for advanced cancers.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, medical oncologists reported using CD4 counts to determine candidacy for systemic therapy; this may inadvertently exclude PLWHC from receiving novel cancer treatments (eg, immunotherapy) or enrolling in clinical trials. 16 Efforts to address these gaps with design of inclusive trials and dissemination of clinical management guidelines are underway. 17 Several oncologists expressed views that appeared to conflate patient risks with stereotypes of PLWH.…”
Section: Discussionmentioning
confidence: 99%
“…[19][20][21] Comparisons between people with and without HIV receiving anti-PD-(L)1 therapies with CD4 1 T-cell counts <350 cells/mL have not shown significant differences in rates of immune-mediated adverse events. 22 There are also data to support the safety of anti-PD-(L)1 agents with chronic infections frequently seen in PWH. For example, there are data for the safe use of these agents in people with HBV receiving concurrent suppressive HBV therapy as well as in people with untreated HCV.…”
Section: Summary Of the Relevant Literaturementioning
confidence: 99%